Evaluation of Fish Biosolids as a Fertilizer for Organic Tomato Transplant Production - Cicely Schembri; Nicholas Kaczmar; John Osborn; Michael B. Timmons; Neil S. Mattson (Horticulturae)
Interest among consumers in the availability of organically produced fruits and vegetables is increasing. Seafood demand is increasingly being met by fish raised using aquaculture methods that provide fish excretory products that can meet organic standards for nutrient sources for organic vegetables. We conducted an experiment in a glass greenhouse to evaluate fish biosolids as a substrate amendment for organic tomato transplant production. We compared the fish biosolids treatment to several different organic fertilizers, along with a commonly used inorganic slow-release fertilizer (Osmocote). All treatments used a target N concentration of 400 mg/L incorporated into the substrate and we also included fish biosolids treatments of 200 and 800 mg N/L. Plant performance was monitored for 4 weeks starting with commercially available 2-week-old seedlings. The results showed that the 800 mg N/L fish biosolids treatment compared very favorably with the conventional Osmocote treatment at the conclusion of the trial. The 800 mg N/L fish biosolids treatment exceeded the Osmocote treatment for chlorophyll content and for leaf number for the first 3 weeks of the 4-week trial. Grower management protocols could further improve seedling performance by providing additional top dressings of fish biosolids or fish effluent waters as plants age.